Development of a hollow cathode neutralizer with the new insert material C12A7:2e− and the corroding effect of the alternative propellant iodine on satellite components - Zschätzsch, Daniel; Justus Liebig University Giessen (My University, 2023)
In recent years, the number of satellites launched into space has exploded. Many of these satellites have electric propulsion systems that run on the common fuel xenon. Xenon is a scarce resource with limited annual production, leading to an unabated increase in the price of xenon per kilogram. Therefore, the transition to alternative propellants is more important than ever. Iodine is one of the most prominent candidates to replace xenon as a propellant in the future. This work addresses the remaining research gaps for the operation of a fully iodine-fueled electric propulsion system and contributes to filling them. The insert materials of conventional hollow cathode neutralizers e.g. LaB6 or Ba-doped W are not compatible with iodine as a propellant during operation. An iodine-compatible alternative insert material is the C12A7:2e− electride of the mayenite C12A7:O2−. In this work, a LaB6 hollow cathode is modified and thermally optimized for operation with the new insert material C12A7:2e−. The hollow cathode modifications successfully prevent the main problem of melting of the insert during operation. In addition, results are presented describing the material behavior of C12A7:2e− during operation while revealing other decomposition processes that lower the operating temperature of C12A7:2e− inserts below the melting temperature. In addition, the corrosion behavior of various structural materials used on satellites in contact with iodine is investigated. The influence of contact of materials with iodine for both iodine vapors, iodine plasma, and iodine ion beams is investigated. Materials studied include various stainless steels and aluminum alloys, as well as elemental samples such as Ni, Cr, Ta, W, Nb, Mo, Al, Fe, and Ti. Unique to this study is that all sample characterization is performed under space conditions and the samples are treated in iodine atmospheres of varying densities typically found in space. In addition, this work presents an approach to scale the iodine erosion effects as a function of the particular atmospheric conditions and exposure times of up to 10 years.
Keywords: Electric propulsion; Hollow cathode; Iodine; Spacecraft; ddc:500; ddc:530